The impact of ewom and perceived quality on purchase intention and purchase decision - Nabila Puji Astuti; Heni Rahayu Rahmawati (FORUM EKONOMI, 2023)
The purpose of this research is to determine the effect of EWOM and Perceived Quality on Purchase Intention and Purchase Decision of Somethinc in Samarinda the type of data used in this research is quantitative data by using primary data and questionnaire is the research instrument. In this research the population is all consumers who have bought and used Somethinc products. The sampling technique used is accidental sampling and data sampling was obtained 102 respondents. The data was collected by using online questionnaire given directly to the respondents via Google Form. Data analysis using multiple linear regression with the help of PLS (Partial Least Square) Version 3. The result obtained shows that (1) EWOM has an insignificant positive effect on Purchase Intention. (2) Perceived Quality has significant positive effect on Purcahse Intention. (3) EWOM has an insignificant positive effect on Purchase Decision. (4) Perceived Quality has significant positive effect onPurchase Decision. (5) Purchase Intention has significant positive effect on Purchase Decision.